وظائف النبر اللغوي في لهجة دمشق - بصل, محمد إسماعيل; بحره, سامر (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
لقد أسهمت الموضوعية التي وسمت (اللسانيات) في تغير كثير من المفاهيم عن اللغة ووظائفها وآثارها في الفرد والمجتمع، وكان من نتائج هذه النظرة الموضوعية المتحررة من سيطرة الموازين المعيارية أن عدت اللهجات، قديمة وحديثة، أنظمة تعبيرية اجتماعية ونماذج لغوية لا تقل عن اللغة الأدبية المشتركة في شيء، من حيث إنها جميعاً تشكل وسائل اتصال إنساني ومدونات لغوية يمكن إخضاعها للدراسة التحليلية اللسانية. وقد دفع ذلك بعض الباحثين إلى دراسة عدد من اللهجات العربية لاكتشاف ما فيها من خصائص في الأصوات والمفردات والتراكيب والدلالات، فهذه اللهجات تمثل تطوراً تاريخياً للهجات القديمة تحرص الأمم الراقية على تسجيله قبل أن يصيبها تطور جديد. إن هذه الدراسة تحاول وصف جانب من جوانب اللهجة الدمشقية فهي دراسة صوتية للنبر اللغوي فيها لاكتشاف قواعده من حيث مواقعه في الكلمات، واستنباط وظائفه من حيث أثره في تكوين الدلالات التي تؤديها الكلمات مفردة أو منظومة في السباق الكلامي. As an objective science, linguistics contributed in changing a lot of concepts concerning language and its functions and effects in both individual and society . This objectivity, uncontrolled by any criterion, resulted in considering the dialects, old and new, social communicative systems and linguistic types equating the common literary language in being communicative means and data that could be analyzed studied linguistically. This encourages some researchers to study some Arabic dialects to discover their sounds, vocabularies, constructions, meanings and other characteristics. These dialects, however show the historical development of the ones which is cautiously registered by civilized nations before they get any further change. This study tries to describe one side of the Damascean dialect. It is a phonological study of the linguistic stress and the rules of its placements in words, as well as, it tries to discover its functions in forming meanings expressed by words isolated or in the context.